Decoloniality, geopolitics of knowledge and historic turn: towards a Latin American agenda. Issue 1 (2nd January 2019) - Wanderley, Sergio; Barros, Amon
Abstract: In this paper, we explore how a decolonial framework can inform management and organizational knowledge (MOK) with the objective of fostering a decolonized historic turn (HT) agenda from Latin America. MOK and the HT are demarcated by the predominance of Anglo-Saxon knowledge in which time fosters a colonizing effect. The HT has not promoted the inclusion of authors, theories, concepts, objects, and themes from other geographies. Hence, we have to make use of geopolitics of knowledge to reintroduce space and to deloconize the HT agenda. We believe that it is by exploring the (dis)encounters of the external and the internal sides of the border, in a double consciousness exercise, that we may foster a more plural field of MOK and a richer HT agenda. From this space of diverse epistemic encounter from both sides of the border, it would be possible to recognize and value what has been produced from the colonial difference, not as expressions of exoticism, but as relevant critical forms of knowledge produced and lived from the perspective of different histories and traditions. More than claims of purism, concepts of anthropophagy and sociological reduction may indicate that Latin America great virtue may be represented by its ability to adapt foreign knowledge to local reality generating something new without letting itself being catechized nor becoming a mimicry copy of the colonizer.